Pneumocystis pneumonia with hypogammaglobulinemia in a pediatric patient who underwent heart transplantation. Issue 4 (4th February 2021) - Takajo, Daiji; Sehgal, Swati; Blake, Jennifer; Aggarwal, Sanjeev
Abstract: A 23‐month‐old Caucasian female who had heart transplantation (HT) at 11 days of age was diagnosed with Pneumocystis pneumonia (PCP) in the setting of secondary hypogammaglobulinemia (HGG). She was diagnosed with HGG at 5 months of age and had been receiving monthly intravenous immunoglobulin infusion. This is the first case report describing the clinical course of PCP in a pediatric patient with HGG. She developed PCP 23 months after HT even when she was off steroids and was receiving timely IVIG. The case posed some clinical questions regarding PCP prophylaxis and HGG management.